Relative orientation between the beta-ionone ring and the polyene chain for the chromophore of rhodopsin in native membranes. - Spooner, P; Sharples, J; Verhoeven, M; Lugtenburg, J; Glaubitz, C; Watts, A (2002)
Rotational resonance solid state nuclear magnetic resonance has been used to determine the relative orientation of the beta-ionone ring and the polyene chain of the chromophore 11-Z-retinylidene of rhodopsin in rod outer segment membranes from bovine retina. The bleached protein was regenerated with either 11-Z-[8,18-(13)C(2)]retinal or 11-Z-[8,16/17(13)C(2)]retinal, the latter having only one (13)C label at either of the chemically equivalent positions 16 and 17. Observation of (13)C selectively enriched in the ring methyl groups, C16/17, revealed alternative conformational states for the ring. Minor spectral components comprised around 26% of the chromophore. The major conformation (approximately 74%) has the chemical shift resolution required for measuring internuclear distances to (13)C in the retinal chain (C8) separately from each of these methyl groups. The resulting distance constraints, C8 to C16 and C17 (4.05 +/- 0.25 A) and from C8 to C18 (2.95 +/- 0.15 A), show that the major portion of retinylidene in rhodopsin has a twisted 6-s-cis conformation. The more precise distance measurement made here between C8 and C18 (2.95 A) predicts that the chain is twisted out-of-plane with respect to the ring by a modest amount (C5-C6-C7-C8 torsion angle = -28 +/- 7 degrees ).